Work Values: Education, Organization, and Religious Concerns - Natale, Samuel M. 19XX-; Rothschild, Brian M.; Sora, Joseph W.; Madden, Tara M. (Value Inquiry Book Series, 1995)
Preliminary Material --Foreword /Samuel M. Natale --Acknowledgements /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --Introduction /William O'Neill and Samuel M. Natale --Section I /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --The Working Class Spirituality /Joseph M. McShane --Comparative Christian Perspectives on the Meaning of Work /Joseph W. Ford --Work, Spirituality, and the Moral Point of View /Kenneth E. Goodpaster --Can Christian Ethics Inform Business Practice?: A Typological Road Map and Criteria of Adequacy for an Ethic of Capitalism /David A. Krueger --The American and Catholic Models of Worker Rights: A Comparison and Appraisal /Michael A. Zigarelli --Section II /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --The Work Ethic and Notions of Character in Scottish Education /W. A. Gatherer --The Multidimensionality of Values Conflicts in the Organizational Life /Michel Dion --New Organizational Structures: A Chance for Workers or a New Mode of Control? /Jacques Delcourt --Defining Forces in Work Attitudes: Cultural Values and Economic Environment /Eduardo S. Paderon and Charles F. O'Donnell --The Growing Dilemma of Loyalty to the Firm /John C. SJ. Haughey --Section III /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --Values/Work/Education: Definitions and Context /Lee J. Richmond --Six Questions for Ethical Educational Management /Michael Bottery --Values Education: A More Effective Route to Managerial Competence? /W. M. Robb --The Educative Dimensions of Workplace Democracy /W.J. Toth --Influences on the Value-Mediating Work of Educational Leaders /K.D. Walker --Personal and Social Education in Vocational Preparation /Richard Pring --Contributors /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --Index /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden --VIBS /Samuel M. Natale , Brian M. Rothschild , Joseph W. Sora , and Tara M. Madden.